2019
DOI: 10.1175/jtech-d-18-0078.1
|View full text |Cite
|
Sign up to set email alerts
|

A Remote Sensing and Atmospheric Correction Method for Assessing Multispectral Radiative Transfer through Realistic Atmospheres and Clouds

Abstract: The ability to quickly and accurately model actual atmospheric conditions is essential to remote sensing analyses. Clouds present a particularly complex challenge, as they cover up to 70% of Earth’s surface, and their highly variable and diverse nature necessitates physics-based modeling. The Laser Environmental Effects Definition and Reference (LEEDR) is a verified and validated atmospheric propagation and radiative transfer code that creates physically realizable vertical and horizontal profiles of meteorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Clouds near the FOV could affect the overall radiance received in the telescope aperture. Future work may consider the effects of clouds on the radiative transfer as other research has successfully demonstrated the efficacy of a systems capable of examining the complex interactions of clouds and atmospheric conditions and their effects on remote sensing systems (Burley et al 2019).…”
Section: E Measurement To Photonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clouds near the FOV could affect the overall radiance received in the telescope aperture. Future work may consider the effects of clouds on the radiative transfer as other research has successfully demonstrated the efficacy of a systems capable of examining the complex interactions of clouds and atmospheric conditions and their effects on remote sensing systems (Burley et al 2019).…”
Section: E Measurement To Photonsmentioning
confidence: 99%
“…Accurate results are possible by capturing the dominant radiometric transfer physics and atmospheric attenuation of each layer. As part of LEEDR's verification and validation Burley et al (2017) made comparisons of LEEDR's calculated sky radiances against measurements in Germany in 2012 (Tohsing et al 2014).…”
Section: Introductionmentioning
confidence: 99%